Implementation of The Pancasila Student Profile Strengthening Project as an Effort to Reinforce Student Character at SDN Trans Buleleng, Morowali Regency - Rizky, Anatriana; Juraid; Hasdin (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to describe the implementation of the Pancasila Student Profile Strengthening Project (P5) as an effort to strengthen the character of students at SDN Trans Buleleng, Morowali Regency. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation. The subjects of the study involved teachers, principals, and students involved in the implementation of the project. The results of the study indicate that the implementation of P5 makes a real contribution to the formation of student character, especially in the dimensions of mutual cooperation, independence, creativity, and critical reasoning. Teachers carry out contextual theme-based projects by involving students in collaborative activities that emphasize the values of Pancasila in an applicable manner in everyday life. However, in the implementation process, several obstacles were still found, such as the lack of training and understanding of teachers regarding the concept and implementation of P5, limited time in integrating project activities into the curriculum, and the less than optimal involvement of parents and the surrounding environment. These obstacles require improvement efforts from various parties so that the implementation of the project can run optimally and sustainably. The conclusion of this study is that the P5 project at SDN Trans Buleleng has had a positive impact on strengthening student character. The success of the program is greatly influenced by the readiness and competence of teachers, support from the principal, and synergy between schools, students, and parents. The implementation of P5 is one of the strategic alternatives in realizing national education goals through a value-based approach.